SMART Research: Toward Interdisciplinary River Science in Europe - Serlet, Alyssa J.; López Moreira M, Gregorio A.; Zolezzi, Guido; Wharton, Geraldene; Hölker, Franz; Gurnell, Angela M.; Tockner, Klement; Bertoldi, Walter; Bruno, Maria Cristina; Jähnig, Sonja C.; Lewandowski, Jörg; Monaghan, Michael T.; et al. (Frontiers in Environmental Science, 2020)
Interdisciplinary science is rapidly advancing to address complex human-environment interactions. River science aims to provide the methods and knowledge required to sustainably manage some of the planet’s most important and vulnerable ecosystems; and there is a clear need for river managers and scientists to be trained within an interdisciplinary approach. However, despite the science community’s recognition of the importance of interdisciplinary training, there are few studies examining interdisciplinary graduate programmes, especially in science and engineering. Here we assess and reflect on the contribution of a 9-year European doctoral programme in river science: ‘Science for MAnagement of Rivers and their Tidal Systems’ Erasmus Mundus Joint Doctorate (SMART EMJD). The programme trained a new generation of 36 early career scientists under the supervision of 34 international experts from different disciplinary and interdisciplinary research fields focusing on river systems, aiming to transcend the boundaries between disciplines and between science and management. We analysed the three core facets of the SMART programme, namely: (1) interdisciplinarity, (2) internationalism, and (3) management-oriented science. We reviewed the contents of doctoral theses and publications and synthesised the outcomes of two questionnaire surveys conducted with doctoral candidates and supervisors. A high percentage of the scientific outputs (80%) were interdisciplinary. There was evidence of active collaboration between different teams of doctoral candidates and supervisors, in terms of joint publications (5 papers out of the 69 analysed) but this was understandably quite limited given the other demands of the programme. We found evidence to contradict the perception that interdisciplinarity is a barrier to career success as employment rates were high (97%) and achieved very soon after the defence, both in academia (50%) and the private/public sector (50%) with a strong international dimension. Despite management-oriented research being a limited (9%) portion of the ensemble of theses, employment in management was higher (22%). The SMART programme also increased the network of international collaborations for doctoral candidates and supervisors. Reflections on doctoral training programmes like SMART contribute to debates around research training and the career opportunities of interdisciplinary scientists.